The Wiley handbook of learning technology - Rushby, Nicholas John; Surry, Daniel W., 1962- (Chichester, UK ; Malden, MA : Wiley Blackwell, 2016)
The Wiley Handbook of Learning Technology is an authoritative and up-to-date survey of the fast-growing field of learning technology, from its foundational theories and practices to its challenges, trends, and future developments. -Offers an examination of learning technology that is equal parts theoretical and practical, covering both the technology of learning and the use of technology in learning -Individual chapters tackle timely and controversial subjects, such as gaming and simulation, security, lifelong learning, distance education, learning across educational settings, and the research agenda -Designed to serve as a point of entry for learning technology novices, a comprehensive reference for scholars and researchers, and a practical guide for education and training practitioners -Includes 29 original and comprehensively referenced essays written by leading experts in instructional and educational technology from around the world.
5.14 2012-14: Big Data and Learning Analytics5.15 Summary; References; Chapter 6 Learning Technology at Home and Preschool; 6.1 Learning Technology; 6.1.1 Defining preschool; 6.1.2 Developmentally appropriate technology; 6.2 Data on Availability and Use of Digital Media; 6.3 The Debates about Young Children and Technology; 6.3.1 Screens and screen time; 6.4 Play and Learning in the Early Years; 6.4.1 Learning; 6.5 Digital Media and Technology in Preschool Settings; 6.5.1 Pedagogy; 6.6 Digital Media and Technology at Home; 6.6.1 Support at home; 6.7 Design; 6.8 Looking Ahead; References
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Educational technology -- Handbooks, manuals, etc; Educational technology; EDUCATION / Administration / General; EDUCATION / Organizations & Institutions; Handbooks and manuals; Electronic books; Electronic books